Transcriptomics-Based Identification of Aquaporin Diversity in the House Dust Mite Dermatophagoides farinae (Acariformes: Pyroglyphidae) - Peng, Jianglong (J Insect Sci, 2018)
Aquaporin water channel proteins are highly conserved across many diverse species. Some evidence indicates that aquaporins in insects may contribute to insect-related mammalian diseases and inflammation, and thus these proteins may represent viable therapeutic targets. Here, we used RNA sequencing and bioinformatics to identify putative aquaporins from the house dust mite, Dermatophagoides farinae. Six putative aquaporins were identified based on sequence similarity with aquaporins from other species. These putative aquaporins, deposited in GenBank and named DerfAQP1–4 (KY231248, KY231249, KY231250, and KY231251, respectively), DerfAQP5.01, and DerfAQP5.02 (KY231252 and KY231253), were successfully cloned into a bacterial plasmid. The identification of full-length aquaporin sequences from D. farinae provides a foundation for future molecular and biochemical studies of these proteins in D. farinae and related species.